Pengaruh Keterlibatan Ayah dalam Pengasuhan Terhadap Kepercayaan diri Anak Usia 5-6 Tahun - Junita Ningsih; Ria Novianti; Hukmi Hukmi (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2026)
A father involvement in child-rearing, when carried out through active and consistent participation, has a positive impact on a child, one of which is self-confidence. Self-confidence is the belief in one’s own potential or abilities, and a child’s self-confidence can influence their character and mental development, which will serve as an important foundation for the child as they face their future, enabling them to respond realistically when facing challenges. The purpose of this study is to determine whether fathers’ involvement in child-rearing has an influence on the self-confidence of 5- to 6-year-old children at TK Education 21 Kulim in Pekanbaru. This is a quantitative study using a regression research design. The study population consists of fathers and their children aged 5–6 years at TK Education 21 Kulim in Pekanbaru. The sampling technique used was saturation sampling, with a sample size of 57 children and 57 fathers. The methods employed in this study included a questionnaire for fathers and an observation sheet for the children. Based on the correlation test calculations, a value of r = 0.653 was obtained, with a significance level of 0.000, indicating a significant influence of fathers’ involvement in child-rearing on the self-confidence of children aged 5–6 years. In conclusion, there is a positive correlation between father involvement in child-rearing and children’s self-confidence at Education 21 Kulim Pekanaru Kindergarten.